COMPARISON OF SMECTITE- AND ILLITE-RICH GOUGE FRICTIONAL PROPERTIES: APPLICATION TO THE UPDIP LIMIT OF THE SEISMOGENIC ZONE ALONG SUBDUCTION MEGATHRUSTS - Saffer D.M.; Marone C. (My University, 2003)
Along plate boundary subduction thrusts, the transformation of smectite to illite within fault gouge at temperatures of ~150°C is one of the key mineralogical changes thought to control the updip limit of seismicity. If correct, this hypothesis requires illite-rich gouges to exhibit frictionally unstable (velocity-weakening) behavior. Here, we report on laboratory experiments designed to investigate the frictional behavior of natural and synthetic clay-rich gouges. We sheared 5-mm-thick layers of commercially obtained pure Ca-smectite, a suite of smectite-quartz mixtures, and natural illite shale (grain size ranging from 2 to 500 μm) in the double-direct shear geometry to shear strains of ~7-30 at room humidity and temperature. XRD analyses show that the illite shale contains dominantly clay minerals and quartz; within the clay-sized fraction (<2 μm), the dominant mineral is illite. thus, we consider this shale as an appropriate analog for fine-grained sediments incoming to subduction zones, within which smectite has been transformed observe a coefficient of friction (μ) 0.42-0.68 illite shale, consistent with previous work. over range normal stresses from 5 150 mpa and sliding velocities 0.1 to 200 μm/s, material exhibits only velocity-strengthening behavior, opposite widely expected, potentially unstablevelocity-weakening behavior sheared under identical conditions low (μ=0.15-0.32) transition velocity weakening at stress strengthening higher (>40 MPa). Our data, specifically the velocity-strengthening behavior of illite shale under a wide range of conditions, do not support the hypothesis that the smectite-illite transition is responsible for the seismic-aseismic transition in subduction zones. We suggest that other depth- and temperature-dependent processes, such as cementation, consolidation, and slip localization with increased shearing, may play an important role in changing the frictional properties of subduction zone faults, and that these processes, in addition to clay mineralogy, should be the focus of future investigation.
Keywords: SUBDUCTION ZONES; FAULT MECHANICS; SEISMOGENIC ZONE; SMECTITE ILLITE; LABORATORY EXPERIMENTS